Applications of Magnetic PsiDO Techniques to Space-adiabatic Perturbation Theory - de Nittis, Giuseppe; Lein, Max (Reviews in Mathematical Physics, 2011)
In this review, we show how advances in the theory of magnetic pseudodifferential operators (magnetic ΨDO) can be put to good use in space-adiabatic perturbation theory (SAPT). As a particular example, we extend results of [24] to a more general class of magnetic fields: we consider a single particle moving in a periodic potential which is subjected to a weak and slowly-varying electromagnetic field. In addition to the semiclassical parameter ε ≪ 1 which quantifies the separation of spatial scales, we explore the influence of an additional parameter λ that allows us to selectively switch off the magnetic field. We find that even in the case of magnetic fields with components in , e.g., for constant magnetic fields, the results of Panati, Spohn and Teufel hold, i.e to each isolated family of Bloch bands, there exists an associated almost invariant subspace of L2(ℝd) and an effective hamiltonian which generates the dynamics within this almost invariant subspace. In case of an isolated non-degenerate Bloch band, the full quantum dynamics can be approximated by the hamiltonian flow associated to the semiclassical equations of motion found in [24].
Keywords: Magnetic field; pseudodifferential operators; Weyl calculus; Bloch electron